(untitled) (Contemporary Journal of Social Science Review, 2025)
This paper explores the diplomatic strategies of the United States and China in the rapidly evolving field of artificial intelligence (AI), focusing on how both countries construct competing narratives of technological sovereignty. Through the lens of Constructivism, the study examines how national identities, perceptions, and ideologies shape foreign policy decisions surrounding AI development and governance. The U.S. positions AI as a tool for promoting democratic values, transparency, and economic growth, while China emphasizes technological self-reliance, state control, and social stability. These contrasting narratives influence their respective approaches to global AI governance, shaping diplomatic engagements and alliances, especially within multilateral platforms such as the G7, BRICS, and the Shanghai Cooperation Organization (SCO). The paper also discusses the broader implications for global governance and the potential fragmentation of AI standards, highlighting the ideological competition between democratic and authoritarian models of AI governance.